Lack of significant effect of therapeutic propranolol on measurable platelet function in healthy subjects. Issue 8 (August 1989) - Pamphilon, D H; Boon, R J; Prentice, A G; Rozkovec, A
Abstract : Propranolol, a non-selective beta blocker, was administered orally in therapeutic doses. The effects of a single dose (160 mg) and one week's treatment (80 mg twice a day) on platelet function were compared in healthy young subjects. There were no significant changes in circulating platelet aggregates, template bleeding time, platelet factor 3 availability and thromboxane beta 2 (TX beta 2) generation. Platelet aggregation responses as assessed by angle of slope and maximal percentage aggregation (all agonists) and lag phase (collagen) showed no changes of biological importance, although minor changes reaching significance were observed with some agonists. These findings suggest that propranolol does not significantly affect platelet function when taken at doses commonly encountered in clinical practice.